Crystallographic properties and oxidation-influenced kinetics of secondary defects in quenched aluminium and aluminium-alloys - Ronander, Einar (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1976.